Advanced control system of DFIG based wind generators for reactive power production and integration in a wind farm dispatching. (15th November 2015) - Ghennam, T.; Aliouane, K.; Akel, F.; Francois, B.; Berkouk, E.M.
Highlights: Modeling of the real and reactive powers production in a wind farm based on DFIG. The wind farm dispatching system sends the power references to each wind turbine. A local power management algorithm is proposed for reactive power production in each generator. Dispatching the power between rotor and stator considering the different operating modes. Implementation of the proposed algorithm on a wind conversion system test bench. Abstract: In this paper, power dispatching of a wind farm is described while focusing on the local power management and controller units of a wind generator. The wind farm dispatching system sends out the appropriate power references to each individual wind generator in order to control the power production of the entire wind farm. A local power management algorithm is proposed for the reactive power production in each wind generator. In fact, this algorithm ensures the management of power references between the Grid Side Converter (GSC) and the DFIG stator circuit by taking into account three modes of the wind farm operating. This algorithm takes also into account the maximum reactive power capability of the DFIG as well as the GSC. The DFIG control system provides the desired power, which is asked by the wind farm dispatching. The proposed reactive power management algorithm and the real and reactive power control for each individual wind generator have been implemented on a dSPACE DS 1104 board. The performance of the reactive power distribution algorithm and the entire DFIG controller are verified through experimental results.